Henry and Mudge and the Starry Night: The Seventeenth Book of Their Adventures - Rylant, Cynthia; Stevenson, Su=cie. (New York : Simon & Schuster Books for Young Readers, 1998)
Henry, his dog Mudge, and his parents go on a quiet camping trip to Big Bear Lake, enjoying the clean smell of trees and wonderful green dreams.
Keywords: Dogs -- Fiction; Camping -- Fiction